Stylistic Features: Conversational Implicature of the Poem “Jabberwocky” by Lewis Carroll - Ni Kadek Dwi Rahayu (Udayana University, 2022)
The present study aimed to analyze the stylistic features especially conversational implicature of the poem “Jabberwocky” written by Lewis Carroll. Implicature theory was the cooperative principle by Paul Grice to use to analyze. Two reasons support to uses of this theory. The method was used Documentation method with note-taking and highlighting technique. First, The poem was taken from the novel entitled Through the Looking-Glass and What Alice Found There. Second, the implied conversation between the characters was found in this poem. This study analyses the violating maxims only. The results were all maxims are violated. Then, Maxim of Quality was mostly violated in this poem.